Proje Yönetimi Eğitiminin Akademik Stres Faktörleri Açısından Değerlendirilmesi. - Geylani, Özlem; Güner, Aysun Ferrah (Electronic Turkish Studies, 2023)
The construction industry's aim is to meet expectations by including management-related courses in universities; engineering management, construction management, and project management (PM) courses, as well as building engineering and architecture disciplines' educational plans. The purpose of the PM knowledge areas included in graduate or undergraduate level courses is to develop students' technical, managerial, and personal skills and to provide a human resource ready to work in the industry. Stress management is one of the responsibilities of project managers in a project team, but human resource development and project success are also important. In this context, in the PM education given at the undergraduate level in architecture faculties, it is important to understand the responses of students to academic stress factors, both for personal development and for the development of the content of the course and the development of the instructors. The study design, after preparing the theoretical background for PM education and academic stress factors in Turkey and the world, identified the relevant topics and prepared a 15-question online survey study. After the pilot survey study conducted by the researchers in an Istanbul-based foundation university where they taught PM courses for three academic periods, 99 student feedbacks were obtained. The scope of the academic stress factors in this study was limited to three academic stress factors that were determined within the scope of the study: the instructor of the course, the language of the course, and the use of a PM software for course submissions. The study also examined the difference in the responses shown during stress according to the gender factor. The data collected was analyzed using the SPSS (Statistical Package for the Social Sciences) package program and the hypotheses proposed in the study were tested. Finally, the study presents the discussion and recommendations based on the findings.